PEMBERDAYAAN GURU MELALUI MODEL “BAHUTE” DALAM MENINGKATKAN ORAL HYGIENE ANAK TUNARUNGU SLB AISYIYAH SINGAPARNA - Rismayani, Lina; Kamelia, Emma; Wahyudin, Wahyudin (Jurnal Abdimas Bina Bangsa, 2024)
The Community Partnership Program (PKM) "Teacher Empowerment Through the 'BAHUTE' Model in Improving Oral Hygiene of Deaf Children at SLB Aisyiyah Singaparna" aims to enhance teachers' ability to teach oral hygiene practices to deaf children. This activity involved 7 teachers and 30 deaf children at SLB Aisyiyah Singaparna. The methods used include counseling, training, and implementation of the BAHUTE (Bacterial Hunting Team) model, a specialized technique designed for cleaning deaf children's teeth. The program was carried out through several stages, including preparation, implementation, and evaluation. Results showed a significant improvement in teachers' knowledge and skills regarding oral hygiene for deaf children. The frequency of children's tooth brushing increased from an average of once to twice daily, and most students were able to demonstrate correct tooth brushing techniques. Routine dental and oral health examinations showed a decrease in cases of dental caries and gingivitis among students. Despite facing some challenges, this program proved effective in improving the oral hygiene of deaf children and has the potential to be implemented in other special education schools across Indonesia.